Perencanaan Penerimaan Pajak Bumi dan Bangunan Perdesaan dan Perkotaan (PBB-P2) pada Badan Pendapatan Daerah Kota Padang Tahun 2021-2023 - Elan Suvindo; Mas Halimah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The objective of this research was to understand the process of planning the Land and Building Tax (PBB-P2) at the Padang City Revenue Agency. The study employed a qualitative descriptive method. Data collection techniques included interviews and documentation. The results of the study depicted that in setting revenue targets for the year 2021-2022, the Padang City Revenue Agency still relied on assumptions without conducting in-depth studies on the actual sources of revenue. In 2023, the Padang City Revenue Agency changed its planning approach by conducting comprehensive analyses of revenue potential based on revenue trends and various alternative efforts to increase revenue. The achievement of the target could be considered a positive accomplishment; however, the fact that the realization was still far below the actual potential indicated that there was still room for improvement in planning. Keywords: Revenue Planning; Rural and Urban Land and Building Tax (PBB-P2); Regional Revenue Agency of Padang City